Fuzzy-set qualitative comparative analysis of implementation outcomes in an integrated mental healthcare trial in South Africa - André Janse van Rensburg; Tasneem Kathree; Erica Breuer; One Selohilwe; Ntokozo Mntambo; Ruwayda Petrus; Arvin Bhana; Crick Lund; Lara Fairall; Inge Petersen (Global Health Action)
Background Integrating mental health services into primary healthcare platforms is an established health systems strategy in low-to-middle-income countries. In South Africa, this was pursued through the Programme for Improving Mental Health Care (PRIME), a multi-country initiative that relied on task-sharing as a principle implementation strategy. Towards better describing the implementation processes, qualitative comparative analysis was adopted to explore causal pathways in the intervention. Objective This study aimed to explore factors that could have influenced key outcomes of an integrated mental healthcare intervention in South Africa. Methods Drawing from an embedded multiple case study design, the analysis used qualitative comparative analysis. Focusing on nine PHC clinics in the Dr Kenneth Kaunda District as cases, with depression reduction scores set as outcome measures, trial data variables were modelled in a hypothetical causal process. A fuzzy-set qualitative comparative analysis was performed by 1) developing the research questions, 2) developing the fuzzy set, 3) testing necessity and 4) testing sufficiency. These steps were undertaken collaboratively among the research team. Results The data were calibrated during several meetings among team members to gain a degree of consensus. Necessity analyses suggested that none of the causal conditions exceeded the threshold of necessity and triviality, and confirmed the inclusion of relevant variables in line with the proposed models. Sufficiency analyses produced two configurations, which were subjected to standard and specific analyses. Ultimately, the results suggested that none of the causal conditions were necessary for a reduction in depression scores to occur, while programme fidelity was identified as a sufficient condition for a reduction in scores to occur. Conclusions The study highlights the importance of understanding implementation pathways to enable better integration of mental health services within primary healthcare in low-to-middle-income settings. It underlines the importance of programme fidelity in achieving the goals of implementation.